Pelestarian Batik Tulis Lasem di Kalangan Perajin Batik Lasem di Desa Babagan Kabupaten Rembang (Equilibrium: Jurnal Pendidikan, 2023)
The purpose of this study was to find out the effort Batik Lasem artist in Babagan village to preserving and maintaining the Lasem batik industry. This study was designed using desriptive qualitative research methods. This study used four samples of artisans namely Batik “Sekar Kencana”, Batik “Kidang Mas”, Batik “Sumber Rejeki” dan  Batik “Sekar Mulyo”. In this study, research data analysis technique uses three component are data reduction, data presentation, and conclusion. The results of this study found that the Batik Lasem artisans in Babagan village still produce and maintain the authencity of Batik Tulis Lasem as did Batik “Sekar Kencana” dan Batik “Kidang Mas”. Beside that, the artisans also made a modification and innovation of Batik tulis Lasem to keep up with the market demand. Other than, artisans of Batik tulis Lasem have used social mediato sell their batik fabrics and as an effort to intoduce Batik tulis Lasem to wider audience. Based on the result, artisans as a agent has a reciprocal relationship with the  social structure in production and reproduction their action in accordance with the theory of structuration. Where the structure as a rule makes artisans still create authentic Batik Lasem to maintain sustainability. But, it also creates a new structure as a “outcome” the reproduction of their action which makes Batik Tulis Lasem  more diverse  and to introduced more widely using social media.
Keywords: Pelestarian; Perajin Batik tulis Lasem; Batik Tulis Lasem; Stukturasi